Implementasi Pada Program Sistem Tanggap Penduduk Pendatang (SIGAP) Versi Mobile dalam Mewujudkan Good Governance di Desa,Kutuh,Kecamatan,Kuta Selatan,Kabupaten,Badung - Navaratri Wibawa, Putu Okky; Supriliyani, Ni Wayan; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT Through the program of Sistem Tanggap Penduduk Pendatang (SIGAP) mobile version, the Kutuh village government seeks to create a digital-based service to realize the concepts of good governance in Kutuh Village. This,research,was,conducted,with descriptive qualitative,method, with,data,collection techniques in the form of interviews with several informants. This research was measured by used.the.theory.of.policy.implementation.(Charles O. Jones) which is consists of 3 (three) indicators namely organization, interpretation, and application. Theresult of the research was indicated the implementation of SIGAP program in Kutuh Village was not run optimally due to several obstacles. There were the obstacles encountered in the implementation of the program namely lack of coordination and communication between Linmas and Panyukertha Desa in carried- out the data collection, SIGAP application having the problems due to unstable signals, and not maximized the socialization of SIGAP program yet. Keywords: Implementation, Innovation Program, Good Governance, Kutuh Village